Rola leasingu w warunkach asymetrii informacji - Kałdoński, Michał (The Role of Leasing under Asymmetric Information, 2006)
In this paper the author shows a rationale for leasing in a setting of asymmetric information where the lessor (manufacturer of capital good) has private information of the asset he leases to the lessee I (user of capital good).The lessee, however, can learn about the quality of his good over the time as he uses the asset. Thus, leasing emerges as a way of mitigating the adverse selection problem. However, another problem is that, since the lessee does not have rights to the residual value of the asset, he has an incentive to use the asset in such a way that he shifts value from the lessor to the lessee. One possibility is that various lessees have different cost of maintaining the capital good. In this case, the higher maintenance cost users have an incentive to devote less care to the maintenance than lower maintenance cost users. Leasing contracts with different provisions can emerge as an equilibrium solution to this double-sided asymmetric information problem in the capital goods market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 296-304